ANALISIS KEMAMPUAN LITERASI MATEMATIKA MAHASISWA DALAM PROSES PEMBELAJARAN DI IAIN TAKENGON - Rosliana Harahap (Jurnal As-Salam, 2020)
Abstract: Mathematical literacy is the capacity of individuals to formulate, use and interpret mathematics in various contexts. Mathematical literacy skills consist of 6 levels, level I, II, and III are low level thinking abilities while level IV, V and VI are high level thinking abilities. These levels can be measured using PISA questions, PISA questions are arranged with content, context and process. Mathematical literacy ability can develop human mindset so that it can find solutions to every problem. This research was conducted to determine the level of literacy ability of students in the first semester of TMA IAIN Takengon TA. 2019 / 2020. This study uses a quantitative description approach. population and sample of 11 students in semester I of TMA IAIN Takengon. The students will be given a math literacy ability test which will be calculated on average. The results of the 11 students' mathematical literacy ability test at level I have an average score of 68.18 so that the mathematics literacy ability of students is in the moderate category, at level II the average score of the student is 69.09 in the medium category, level III average score students are 67.72 in the medium category, the average level IV score of students is 51.81 in the low category, at level V the average score of students is 45 in the low category and at level VI the average score of students is 28.63 in the category low. And the score of 11 students' mathematical literacy ability is 55,076 in the low category. Because the overall mathematical literacy ability of students in the category is low so it must be done innovation and development of appropriate learning models so that students' mathematical literacy skills are even better. Keywords: Literacy ability, Mathematics, PISA Abstrak: Kemampuan literasi matematika adalah kapasitas individu untuk memformulasikan, menggunakan, dan menafsirkan matematika dalam berbagai konteks. Kemampuan literasi matematika dapat mengembangkan pola pikir manusia sehingga dapat menemukan solusi dari setiap masalah. Penelitian ini dilakukan untuk mengetahui tingkat kemampuan literasi mahasiswa semester I TMA IAIN Takengon TA. 2019/2020. Penelitian ini menggunakan pendekatan deskripsi kuantitatif. Dengan populasi dan sampel seluruh mahasiswa semester I TMA IAIN Takengon yang berjumlah 11 orang. Mahasiswa akan diberikan tes kemampuan literasi matematika yang selanjutnya nilainya akan dihitung rata-ratanya. Hasil tes kemampuan literasi matematika 11 mahasiswa tersebut pada level I memilki rata-rata nilai 68,18 sehingga kemampuan literasi matematika mahasiswa dalam kategori sedang, pada level II rata-rata hasil tes kemampuan literasi matematika mahasiswa adalah 69,09 dalam katerogi sedang, pada level III nilai rata-rata hasil tes kemampuan literasi matematika mahasiswa adalah 67,72 dalam kategori sedang, pada level IV rata-rata nilai hasil tes kemampuan literasi matematika mahasiswa adalah 51,81 dalam kategori rendah, pada level V nilai rata-rata kemampuan literasi matematika mahasiswa adalah 45 dalam kategori rendah dan pada level VI rata-rata nilai kemampuan literasi matematika mahasiswa adalah 28,63 dalam kategori rendah. Dan nilai rata-rata kemampuan literasi matematis 11 mahasiswa tersebut adalah 55,076 dalam kategori rendah. Karena kemampuan literasi mahasiswa matematika dalam kategori rendah maka perlu dilakukan inovasi pembelajaran yang dapat meningkatkan kemampuan literasi matematika mereka. Kata Kunci : Kemampuan literasi, Matematika, PISA